Textured Sb2Te3 films and GeTe/Sb2Te3 superlattices grown on amorphous substrates by molecular beam epitaxy - Jos E. Boschker; E. Tisbi; E. Placidi; Jamo Momand; Andrea Redaelli; Bart J. Kooi; Fabrizio Arciprete; Raffaella Calarco (AIP Advances, 2017)
The realization of textured films of 2-dimensionally (2D) bonded materials on amorphous substrates is important for the integration of this material class with silicon based technology. Here, we demonstrate the successful growth by molecular beam epitaxy of textured Sb2Te3 films and GeTe/Sb2Te3 superlattices on two types of amorphous substrates: carbon and SiO2. X-ray diffraction measurements reveal that the out-of-plane alignment of grains in the layers has a mosaic spread with a full width half maximum of 2.8°. We show that a good texture on SiO2 is only obtained for an appropriate surface preparation, which can be performed by ex situ exposure to Ar+ ions or by in situ exposure to an electron beam. X-ray photoelectron spectroscopy reveals that this surface preparation procedure results in reduced oxygen content. Finally, it is observed that film delamination can occur when a capping layer is deposited on top of a superlattice with a good texture. This is attributed to the stress in the capping layer and can be prevented by using optimized deposition conditions of the capping layer. The obtained results are also relevant to the growth of other 2D materials on amorphous substrates.